Image Compression based on Octagon Based Intra Prediction - et. al., S.Anitha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently image coding has been an important research area in many fields. Various compression algorithms have been developed in different ways for image compression. One of the ways in image coding is prediction based image coding. This paper proposes a novel technique for finding the prediction of a current pixel. Instead of traditional four mode prediction, this paper proposes an eight mode prediction scheme. The proposed method is tested with nine traditional images and compared with four recent methods. Experimental results substantially proved that the proposed method is better than recent methods..